PERBANDINGAN RETURN DAN RISK SAHAM SYARIAH DENGAN SAHAM NON SYARIAH SELAMA PANDEMI COVID-19 DI INDONESIA (Studi Kasus pada Jakarta Islamic Index dan IDX30) - Verna Diarawati; Maslichah Maslichah (Universitas Islam Malang, 2021)
This study aims to find out the comparison and analysis of return and risk of sharia stocks with non-sharia stocks during the covid-19 pandemic in Indonesia precisely in January to June 2020 with case studies on the Jakarta Islamic Index and IDX30. This research is a quantitative research with a type of comparative descriptive research that is research by comparing one or more variables against different samples, which use return and risk on JII index, and IDX30 Index as a comparison. In quantitative research, sample determination can use a purposive sampling method with 14 companies registered in Jakarta Islamic Index (JII) and 10 companies listed on IDX30 index. The results of this study showed that from the Independent Sample t Test hypothesis test that there is no significant difference between the return and risk of sharia stocks and non-sharia stocks that are consistent in the list of JII index and IDX30 index.Keywords: Return, Risk, sharia stocks, non-sharia stocks